Modelling and Simulation of a Fuzzy System for Site-Specific Nitrogen Fertilization. Issue 2 (2020) - Heiß, Andreas; Paraforos, Dimitrios S.; Sharipov, Galibjon M.; Griepentrog, Hans W.
Abstract: Increasing environmental concerns are a driving force in the search for ways to improve the efficiency of mineral nitrogen (N) fertilization. Spectral sensors to determine the crop's supply status are among the most mature precision agriculture technologies to adapt the N dose site-specifically to the crop's need. By using artificial intelligence techniques like expert systems based on fuzzy set theory, the algorithms of such sensor systems could be adapted by the farmer to the highly varying conditions among the specific fertilization dates. This paper is dealing with the development of a fuzzy logic based model of the commercial Yara N-Sensor's dosing algorithms. Simulations for several sets of input-output data acquired in field experiments showed high accordance with the behaviour of the N-Sensor system with good adaptability to different calibrations.